From Learning to Submission: Silenced Pedagogy, AI Dependency, and Chronemic Neglect in Distance Higher Education - Fauzan Fauzan (CV. Bunda Ratu, 2026)
The rapid integration of Generative Artificial Intelligence (GenAI) into distance education has created a strange contradiction: while accessing information has never been easier, genuine student engagement seems to be slipping away. This qualitative study introduces the concept of Silenced Pedagogy—a condition where meaningful teaching dialogue fades not because instruction has stopped, but because students are increasingly checking out of the learning process through heavy AI reliance and what we call chronemic neglect. Using Interpretative Phenomenological Analysis (IPA), we explored the experiences of fourteen online instructors at Universitas Terbuka, Indonesia.Three interconnected themes emerged from our analysis. First, instructors described encountering *ghost scholars*—students whose assignments showed polished language but little evidence of real intellectual effort, personal reflection, or genuine engagement with the material. Second, teachers observed what we term ritualized bad-faith negotiations, where requests for deadline extensions and academic accommodations became increasingly performative and transactional rather than meaningful. Third, participants reported an *erosion of pedagogical agency*, marked by hermeneutic fatigue, diminished professional satisfaction, and growing uncertainty about whether their assessments still held educational value. There are three interrelated issues occurred with the analysis. First, teacher found “ghost Scholar” it means the students who prepared the assignment with AI completely assisted Our findings suggest that when AI dependency and chronemic neglect converge, the problems extend far beyond academic integrity concerns. Together, these factors weaken the back-and-forth processes of inquiry, reflection, feedback, and meaning-making that genuine learning depends on. To explain this phenomenon, we propose the framework of Silenced Pedagogy, showing how cognitive offloading, temporal disengagement, and transactional approaches to learning interact to undermine the instructor-student relationship in distance education. We discuss practical implications for process-oriented assessment, more reciprocal feedback practices, flexible temporal learning arrangements, and institutional AI literacy initiatives in open and distance learning contexts.